1975
DOI: 10.1121/1.380781
|View full text |Cite
|
Sign up to set email alerts
|

Difference frequency pressure within the interaction region of a parametric array

Abstract: A theoretical model that predicts difference frequency pressure within the interaction region of a parametric array is presented. Linear and nonlinear attenuation are neglected, and it is assumed that the primary signals are spherically spreading throughout the interaction region. It is shown that with these assumptions the three-dimensional scattering integral can be reduced to a single integral if the primary pressure fields are axially symmetric. Analyses of the error introduced by assuming the primary fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Accordingly, we searched for a signal at the difference frequency that occurred when the frequencies of the driving transducers were varied. A second criterion is that the amplitude of the difference frequency beam Aa• c should be proportional to the product of the amplitudes of the driving signals [Jones and Kobett, 1963;Rolleigh, 1975]. Because these two tests did not necessarily distinguish between nonlinear signals originating in the rock and those produced in the external transducers and electronics or through surface wave interaction, we also checked for directional effects.…”
Section: Observation Of Collinear Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we searched for a signal at the difference frequency that occurred when the frequencies of the driving transducers were varied. A second criterion is that the amplitude of the difference frequency beam Aa• c should be proportional to the product of the amplitudes of the driving signals [Jones and Kobett, 1963;Rolleigh, 1975]. Because these two tests did not necessarily distinguish between nonlinear signals originating in the rock and those produced in the external transducers and electronics or through surface wave interaction, we also checked for directional effects.…”
Section: Observation Of Collinear Mixingmentioning
confidence: 99%
“…The signal at the difference frequency Aris of particular interest since its amplitude decays more slowly with distance because of its longer wavelength. Thus despite the fact that the energy conversion from the primary input beams to the difference frequency beam is inefficient [Taylor and Rollins, 1964], the combined effects of collimation and lower spatial attenuation produce a useful low-frequency acoustic source; exploitation of nonlinear beam generation has led to develCopyright 1987 by the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%
“…However, Rolleigh [5] proved that the error introduced by approximating these collimated plane waves by spherical waves inside the Rayleigh distance R P at the primary frequency is negligible if the observation point is slightly beyond R P . The calculation of the three-dimensional integral is accomplished in the MATLAB environment.…”
Section: Theorymentioning
confidence: 99%
“…It is found that the suggested method for the three-dimensional numerical integration has good convergence. Rolleigh [21] pointed out that there were controversial results concerning the di!erence frequency beamwidth of parametric arrays. For instance, Rolleigh's results show a decrease in di!erence frequency beamwidth as the observation distance increases.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation